Two-phase micro-electromembrane extraction with a floating drop free liquid membrane for the determination of basic drugs in complex samples - Šlampová, Andrea; Kubáň, Pavel (Talanta, 2020)
A two-phase micro-electromembrane extraction (μ-EME) using a floating drop of an organic solvent was presented for rapid and efficient pretreatment of complex biological samples. The μ-EME system consisted of a glass vial containing aqueous sample (donor solution) and a small drop of a water-immiscible organic solvent (4-nitrocumene), which was floating on the surface of the aqueous solution in form of a free liquid membrane (FLM). The vial geometry and the optimized volume ratios of the donor and the FLM ensured a stable position of the FLM in the center of the vial during μ-EME, and one electrode of a d.c. power supply was inserted directly into the FLM while the other electrode was placed into the aqueous sample. The active surface area of the floating drop FLM contacting the sample was considerably larger in comparison to formerly reported μ-EME formats employing FLMs and resulted in a faster and a more efficient transfer of target analytes from the sample to the FLM. Four basic drugs (nortriptyline, papaverine, loperamide, and haloperidol) were selected as model analytes and were extracted from physiological solution, human urine, and dried blood spot samples. At the optimized μ-EME conditions (250 V, 15 min, 300 rpm, acidic donor) and the optimized ratio of the sample to the FLM volume (500:14 μL), extraction recoveries between 49 and 100% and enrichment factors up to 35.7 were achieved. Quantitative analyses of the basic drugs in the resulting FLMs (diluted with methanol) were performed by capillary electrophoresis with ultraviolet detection and demonstrated excellent repeatability (RSD ≤ 4.9%) and linearity (r2 ≥ 0.9997), and low limits of detection (5-28 ng/mL) of the method.